Confronting the Robinson Crusoe paradigm with household-size heterogeneity - Christos Koulovatianos; Carsten Schröder; Ulrich Schmidt (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Modern macroeconomics empirically addresses economy-wide incentives behind economic actions by using insights from the way a single representative household would behave. This analytical approach requires that incentives of the poor and the rich are strictly aligned. In empirical analysis a challenging complication is that consumer and income data are typically available at the household level, and individuals living in multimember households have the potential to share goods within the household. The analytical approach of modern macroeconomics would require that intra-household sharing is also strictly aligned across the rich and the poor. Here we have designed a survey method that allows the testing of this stringent property of intra-household sharing and find that it holds: once expenditures for basic needs are subtracted from disposable household income, household-size economies implied by the remainder household incomes are the same for the rich and the poor.
urn:nbn:de:hebis:30-56972
Keywords: C42; E21; D12; E01; D11; D91; D31; I32; 330; Linear Aggregation; Representative Consumer; Equivalence Scales; Survey Method; Household-Size Economies; Konsumentenverhalten; Haushaltsökonomik; Verbraucherausgaben; Skalenertrag; Disparitätsmaß; Schätzung; USA